LC–MS/MS strategies for therapeutic antibodies and investigation into the quantitative impact of antidrug-antibodies. (December 2016) - Ewles, Matthew; Mannu, Ranbir; Fox, Chris; Stanta, Johannes; Evans, Graeme; Goodwin, Lee; Duffy, James; Bell, Len; Estdale, Sian; Firth, David
Aim: We aimed to establish novel, high-throughput LC–MS/MS strategies for quantification of monoclonal antibodies in human serum and examine the potential impact of antidrug antibodies.Methodology: We present two strategies using a thermally stable immobilized trypsin. The first strategy uses whole serum digestion and the second introduces Protein G enrichment to improve the selectivity. The impact of anti-trastuzumab antibodies on the methods was tested.Conclusion: Whole serum digestion has been validated for trastuzumab (LLOQ 0.25 µg/ml). Protein G enrichment has been validated for trastuzumab (LLOQ 0.1 µg/ml), bevacizumab (LLOQ 0.1 µg/ml) and adalimumab (LLOQ 0.25 µg/ml). We have shown the potential for anti-drug antibodies to impact on the quantification and we have subsequently established a strategy to overcome this impact where total quantification is desired.